Japan's wooden heritage a journey through a thousand years of architecture - Fujimori, Terunobu 1946-; Fujitsuka, Mitsumasa 1939-; Larrabee, Hart (Tokyo Japan Publishing Industry Foundation for Culture, 2017)
"Japan's Wooden Heritage: A Journey Through a Thousand Years of Architecture brings together essays by architectural historian Terunobu Fujimori and photographs by Mitsumasa Fujitsuka, and commentary by structural engineer Mikio Koshihara that originally appeared in Kateigah?ao, Japan's premier magazine of art and culture, supplemented with additional essays by Mitsumasa Fujitsuka. What distinguishes this volume is its selection of 23 locations--including well-known temples and shrines but also lesser-known structures--to represent a broad scope of architectural styles, functions, and time periods; the outstanding photographs; and the distinct approaches taken by each of the three essayists"-- Publisher's description.
The Jåodo-dåo (Pure Land Hall) at Jåodo-ji Temple -- The Håoåo-dåo (Phoenix Hall) at Byåodåo-in Temple -- Kintai-kyåo Bridge -- Matsumoto Castle -- åOtaki Shrine -- The Nakamura House at Narai-juku -- The Zaåo-dåo Hall at Kinpusen-ji Temple -- The old Konpira Grand Theatre (Kanamaru-za) -- The Goshadåo of Akagami Shrine -- Rinshun -kaku Villa -- Nageire-dåo Hall -- Covered bridges -- The Sanjåusangen-dåo Hall (Rengeåo-in Temple) -- The main hall at Izumo Taisha Shrine -- The Kannon-dåo Hall at Kasamori- ji Temple -- Seison-kaku Villa -- The Aizu Sazae-dåo Hall -- The ferryman's hut at Suge -- The åO-dåo (Great Hall) at Fuki-ji Temple -- The five-tiered pagoda at Rurikåo-ji Temple -- The Tsubokawa House -- The Jo-an Tea Ceremony House -- Itsukushima Shrine -- Wooden Heritage seen with as architectonic eye.
"This book is a translation of Nihon mokuz?ao isan : sennen no kenchiku o tabi suru (Sekai Bunka Publishing, Inc., 2014), which compiled a series of articles--planned and photographed by Mitsumasa Fujitsuka and written by Terunobu Fujimori with commentary by Mikio Koshihara--that were originally published in Kateigah?ao magazine, supplemented with additional essays by Mitsumasa Fujitsuka"--Page 002.
Text translated into English from Japanese.
Keywords: Vernacular architecture -- Japan; Wooden-frame buildings -- Japan -- History; Architecture -- Japan -- History -- To 1868.